Latissimus dorsi rotational flap combined with a custom-made scapular prosthesis after oncological surgical resection: a report of two patients - Giovanni Beltrami; Gabriele Ristori; Guido Scoccianti; Angela Tamburini; Rodolfo Capanna; Domenico Campanacci; Marco Innocenti (BMC Cancer, 2018)
Abstract Background Sarcomas that arise from the scapula or periscapular soft tissues often require a total scapulectomy. This often implies a large complex tissue defect that needs adequate reconstruction of both bone and soft tissue. Although various methods have been developed, no optimal procedure has emerged. Postoperative complications are common and functional recovery is not always satisfactory. This study aims to present a new surgical technique that combines a custom-made scapular prosthesis with a functional latissimus dorsi flap. Case presentation Two patients diagnosed with malignant tumour of the scapular region were surgically treated after proper multidisciplinary evaluation. The first patient underwent the procedure as a first surgery, the second as revision surgery. The new technique comprises three surgical stages: excisional surgery with soft tissue resection and scapulectomy, bone reconstruction with custom-made prosthesis, and soft tissue reconstruction using a latissimus dorsi rotational flap overturned on the prosthesis. The goal is to set up a new functional unit combining an anatomically shaped implant (manufactured using latest three-dimensional printing technology) and a muscular flap, and to maintain the neurovascular supply. The patients were followed up to evaluate functional outcome and complications. Both patients were alive with no evidence of disease. Functional results were satisfactory and the Musculoskeletal Tumor Society scores were 87% and 63%, respectively. No surgical complications such as implant breakage, joint collapse, wound dehiscence, or infection were observed. Conclusions This new technique upgrades the role of the latissimus dorsi flap to a functional tool in combination with an anatomical, three-dimensionally printed, custom-made prosthesis, and provides adequate well-vascularized and healthy tissue to maximize the likelihood of successful limb salvage.